The Interest Of Accounting Students To Become External Auditors - Mafazah, Syifa Nur; Baridwan, Zaki (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This quantitative study aims to explore the factors influencing accounting students’ interest in pursuing a career as an external auditor. It examines the impact of labor market considerations, social values, professional training, family environment, and gender. The research employed a purposive sampling technique, selecting 111 accounting students from the seventh to fourteenth semester at the Faculty of Economics and Business, Universitas Brawijaya (DAFEB UB), who had completed internships as external auditors. Data was collected through Google Form questionnaires and analyzed using IBM SPSS 26 software. The findings reveal that labor market considerations, professional training, and family environment have a positive influence on the students' career interest in becoming external auditors. On the other hand, social values and gender were found to have a negative impact on their career interest. This study hopes that students will actively engage in their coursework and participate in training or seminars both at the university and outside of it. This is important to help ease their career development after graduation by enhancing the competencies they have gained, supported by relevant stakeholders.